Understanding Why Frequent Users of EMS Call 9-1-1: A Grounded Theory Study. Issue 3 (May 2020) - Mahmuda, Sabnam; Wade-Vallance, Adam; Stosic, Alix; Guenter, Dale; Howard, Michelle; Agarwal, Gina; McLeod, Brent; Angeles, Ricardo
Introduction. Frequent users of emergency medical services (EMS) have disproportionately high 9-1-1 call frequency. Evidence suggests that this small group burdens the health care system, leading to misallocation of already-limited health resources. Aim. To understand frequent users' perceptions and experiences regarding EMS, as well as the driving factors underlying their frequent use. Method. A grounded theory approach guided our qualitative research process. Participants older than 17 years who called EMS five or more times in the past year were consecutively sampled where each participant was contacted in the order they appeared on our list of potential participants for interviews until data saturation was achieved. Transcripts were analyzed to derive common themes among frequent EMS callers. Results. Frequent EMS calls often resulted from chronic medical conditions creating recurrent crisis situations, mental health issues as well as mobility issues, frequent noninjurious falls, and social isolation. Combined with these factors, perceptions of the purpose of EMS and social circumstances also contributed to the creation of complex health issues that influenced frequent EMS use. These findings can advise the development of future paramedicine programs and health promotion interventions.